The Roles of Entrepreneurship Knowledge, Self-Efficacy, Family, Education, and Gender on Entrepreneurial Intention - Hutasuhut, Saidun (Dinamika Pendidikan, 2018)
This research aims to analyze whether knowledge of entrepreneurship, self-efficacy, family factors and educational background affect intention of student’s entrepreneurship and roles of gender moderator on the influence of entrepreneurial knowledge on student’s entrepreneurial intention. This research was conducted on students of Economics Faculty, Universitas Negeri Medan with a population of 2732 students in the odd semester of 2017. 349 students were analysed as sample and used simple random sampling technique, but the eligible sample were 319 students. It was measured by using Slovin Formula. 6 study programs of Economics Faculty i.e. Accounting, Management, Education Administration Office, Accounting Education, Economic Education, and Education of Commerce used as sample. Data collection of entrepreneurial knowledge, self-efficacy, and entrepreneurial intention were collected by using instruments; while data of family background, educational background, and gender were obtained from the identity of the respondents. Data analysis techniques used multiple regression and Moderated Regression Analysis (MRA). The research finding is entrepreneurial knowledge, self-efficacy, and family factor have a significant impact on student’s entrepreneur intention respectively. The educational background variable does not affect the entrepreneurial intention. While gender is not as a moderating variable on the influence of entrepreneurial knowledge on entrepreneurial intention.